Over the Horizon Proliferation Threats. - Wirtz, James (Stanford University Press, 2012)
In every decade of the nuclear era, one or two states have developed nuclear weapons despite the international community's opposition to proliferation. In the coming years, the breakdown of security arrangements, especially in the Middle East and Northeast Asia, could drive additional countries to seek their own nuclear, biological, or chemical (NBC) weapons and missiles. This likely would produce greater instability, more insecure states, and further proliferation. Are there steps concerned countries can take to anticipate, prevent, or dissuade the next generation of proliferators? Are ther.